China's emerging middle class : beyond economic transformation - Li, Cheng, 1956- (Brookings Institution Press, 2010)
As recently as two decades ago there was no distinct middle class in the People's Republic of China. Today, any meaningful discussion of China's economy, politics, or society must take into account the rapid emergence and explosive growth of the Chinese middle class. Cheng Li, a Brookings scholar and noted expert on China, leads a team of experts in detailing the origins and characteristics of this dramatic change, assessing its current effects on Chinese society and discussing what it portends for the future.